A Phase II Trial of the Double Epigenetic Priming Regimen Including Chidamide and Decitabine for Relapsed/Refractory Acute Myeloid Leukemia - Jia Yin; Jia Yin; Chao-Ling Wan; Chao-Ling Wan; Ling Zhang; Ling Zhang; Hao Zhang; Lian Bai; Hai-Xia Zhou; Hai-Xia Zhou; Ming-Zhu Xu; Ming-Zhu Xu; et al. (Frontiers in Oncology, 2021)
ObjectiveTo explore the role of chidamide, decitabine plus priming regimen in the salvage treatment of relapsed/refractory acute myeloid leukemia.MethodsA clinical trial was conducted in relapsed/refractory acute myeloid leukemia patients using chidamide, decitabine, cytarabine, idarubicin, and granulocyte-colony stimulating factor, termed CDIAG, a double epigenetic priming regimen.ResultsThirty-five patients were recruited. Three patients received 2 treatment cycles. In 32 evaluable patients and 35 treatment courses, the completed remission rate (CRR) was 42.9%. The median OS time was 11.7 months. The median OS times of responders were 18.4 months, while those of nonresponders were 7.4 months (P = 0.015). The presence of RUNX1 mutations was associated with a high CRR but a short 2-year OS (P = 0.023) and PFS (P = 0.018) due to relapse after treatment. The presence of IDH mutations had no effect on the remission rate (80.0% vs. 73.3%), but showed a better OS (2-year OS rate: 100.0% vs. 28.9%). Grade 3/4 nonhematological adverse events included pneumonia, hematosepsis, febrile neutropenia, skin and soft tissue infection and others.ConclusionThe double epigenetic priming regimen (CDIAG regimen) showed considerably good antileukemia activity in these patients. Adverse events were acceptable according to previous experience. The study was registered as a clinical trial.Clinical Trial Registrationhttps://clinicaltrials.gov/, identifier:NCT03985007